ANALYSIS OF GRADE XI STUDENTS’ DIFFICULTIES IN SOLVING MATH STORY PROBLEMS BASED ON CRITICAL THINKING SKILLS - Fajriani, Nur; Subawo, Made; Haidar, Irajuana (JME (Journal of Mathematics Education), 2025)
This descriptive study aims to analyze students' difficulties in solvingmathematical word problems based on their critical thinking skills. Thestudy was conducted at SMA Negeri 1 Tanggetada, involving 26 studentsas research subjects using purposive sampling technique. Several studentsrepresenting different categories of critical thinking skills were selectedfor interviews based on their test results. The results showed that, onaverage, students experienced a 68.97% difficulty level across allindicators, indicating a high category of difficulty. Among the indicators,students had the greatest difficulties in drawing conclusions (93.59%) andperforming calculation operations (87.18%). Furthermore, the students’critical thinking skills were found to be very low, with an average score of10.9.